2014
DOI: 10.1007/s10072-014-1758-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic headaches: a clinical overview

Abstract: Headache attributed to head and/or neck trauma or injury, the so-called post-traumatic headache (PTH), is the most common secondary headache disorder and one of the most controversial clinical entities in the headache field, due to its unclear pathophysiological mechanisms and the unsolved role of associated psychological and medico-legal aspects. PTH, as a significant cause of morbidity after traumatic brain injury, may occur as an isolated symptom or as one of a constellation of symptoms known as post-concus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Lastly , PTH patients often present with a plethora of symptoms (i.e. fatigue, depression, sleep disturbances) and not only headache [2, 22]. It would be interesting if future RCTs and high-quality open-label studies included secondary endpoints set to investigate drug efficacy on factors such as health-related quality of life, work productivity and levels of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly , PTH patients often present with a plethora of symptoms (i.e. fatigue, depression, sleep disturbances) and not only headache [2, 22]. It would be interesting if future RCTs and high-quality open-label studies included secondary endpoints set to investigate drug efficacy on factors such as health-related quality of life, work productivity and levels of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of PTH and underlying mechanisms by which a concussive injury may lead to new or exacerbated headache are poorly understood. Headache specifically occurring or worsening immediately after TBI is often classified as a unique headache syndrome that may have a partially distinct etiology due to biomechanical forces on the musculoskeletal system and resultant neural changes occurring during or shortly after head injury . However, inconsistency of associations between headache and indicators of brain damage suggest that these mechanisms may not account for headache in all (or even most) cases .…”
Section: Introductionmentioning
confidence: 99%
“…Headache specifically occurring or worsening immediately after TBI is often classified as a unique headache syndrome that may have a partially distinct etiology due to biomechanical forces on the musculoskeletal system and resultant neural changes occurring during or shortly after head injury. 13,14 However, inconsistency of associations between headache and indicators of brain damage suggest that these mechanisms may not account for headache in all (or even most) cases. 15 For example, some studies have found a positive relationship between PTH and loss of consciousness (LOC), an index of TBI severity, 16 while other studies have shown that greater LOC is inversely associated with PTH.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, research has largely focused on examining predictors of post‐traumatic headache (PTH) after mild traumatic brain injury (mTBI). These studies suggest that female sex, pre‐existing psychiatric or behavioral conditions, and prior history of headache strongly predict PTH after mTBI. Additionally, postinjury PTSD contributes to chronic or worsening PTH through 1 year post‐mTBI .…”
Section: Acute Headache–psychiatric Comorbiditymentioning
confidence: 99%
“…Together, the psychiatric comorbidity (eg, PTSD, depression, and anxiety) associated with headache pain likely conveys amplified vulnerability to the development of health problems and impairment following injury . Byllesby et al recently noted that this comorbidity presents challenges for differential diagnosis, especially among generalized distress or negative affect‐related disorders.…”
mentioning
confidence: 99%